2011
DOI: 10.1143/jjap.50.095601
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Epitaxial Graphene Growth by Si Sublimation from SiC(0001) Surface

Abstract: One-dimensional tilted carbon nanorod arrays were synthesized on molybdenum substrates by using the catalyst-assisted oblique angle deposition technique. The structures of the one-dimensional tilted carbon nanorods evolve with substrate temperatures, but otherwise identical growth conditions. The crystallographic structures, chemical compositions and bond structures of the tilted carbon nanorods were investigated by using x-ray diffraction, energy dispersive x-ray spectroscopy, x-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…However, generally speaking, Si sublimation cannot be limited to the steps and the C supply is not necessarily abundant. Therefore, next we assume that Si atoms sublimate from a terrace and no excess C atoms are supplied from anywhere else, and compare the two results [25].…”
Section: Epitaxial Graphene Growth On a Flat Surfacementioning
confidence: 99%
“…However, generally speaking, Si sublimation cannot be limited to the steps and the C supply is not necessarily abundant. Therefore, next we assume that Si atoms sublimate from a terrace and no excess C atoms are supplied from anywhere else, and compare the two results [25].…”
Section: Epitaxial Graphene Growth On a Flat Surfacementioning
confidence: 99%
“…We work out the associated energy barriers characterizing the possible reaction paths, tracking the processes that lead to the formation of the initial carbon seeds from which graphene can subsequently grow. Former DFT calculations for carbon layers on SiC(0001) were focused mainly on the structural stability of a selected set of carbon overlayers and, as such, they provide little information about the actual reaction mechanisms. From the experimental observation described above, the essential and basic processes of the graphene growth seem to be summarizable in two stages: (i) Si atoms are desorbed from the nanofacet; that is, the bunched atomic steps, migrate to the terrace sites, and are eventually sublimated.…”
Section: Introductionmentioning
confidence: 99%
“…Calculations have shown that Si vacancies or C interstitial in the interface layer below the BG o layer lead to lower total surface energies that can give rise to a number of possible large BG o corrugations. 40 Besides the high Si vacancy concentration, there is a significant change in the carbon-silicon spacing in the top SiC bilayer. The C-Si z-spacing, ∆ Si-C , in the SiC bilayer below BG o is 30% shorter compared to a bulk SiC bilayer and half the distance predicted by ab initio calculations in a bulk terminated surface with a BG ML +ML film.…”
Section: Z-zs1(å) σ(å) θ(Mlg)mentioning
confidence: 99%